Effects of layer thickness on desiccation cracking behaviour of a vegetated soil - Congying Li; Qing Cheng; Chaosheng Tang; Yingdong Gu; Lingxin Cui; Haowen Guo (Biogeotechnics)
The objective of this study is to explore how different layer thicknesses affect the desiccation cracking behaviour of vegetated soil. During the experiment, an electronic balance was employed to quantify water evaporation, while a digital camera was utilized to capture the initiation and progression of soil surface cracking. Results indicate that in the early drying process, the rate of evapotranspiration in vegetated soil correlates positively with leaf biomass. For soil samples with the same layer thickness, the constant rate stage duration is consistently shorter in vegetated soil samples than in their bare soil counterparts. As the layer thickness increases, both vegetated and bare soil samples crack at higher water content. However, vegetated soil samples crack at lower water content than their bare soil counterparts. Vegetation significantly reduces the soil surface crack ratio and improves the soil crack resistance. The crack reduction ratio is positively correlated with both root weight and length density. In thicker vegetated soil layers, the final surface crack length noticeably declines.